INTERLAYER STRUCTURE IN ASPIDOLITE, THE NA ANALOGUE OF PHLOGOPITE - Kogure T.; Banno Y.; Miyawaki R. (My University, 2004)
It has been found that aspidolite, the Na analogue of phlogopite, has an unusual interlayer structure for micas. The aspidolite investigated is interleaved with phlogopite in a thermally metamorphosed rock. Electron microprobe chemical analyses showed similar compositions for aspidolite and phlogopite except interlayer cations of sodium and potassium. High-resolution transmission electron microscopy (HRTEM) revealed that the direction of the intralayer shift (shift between the two tetrahedral sheets in a 2:1 layer) is uniform, a/3 toward [(1) over bar 00], for all 2:1 layers, and that sodium and potassium are resolved to different interlayer regions to form interstratification of the two micas at monolayer level. HRTEM and electron diffraction analyses indicate a large layer offset, i.e., lateral shift between the two tetrahedral sheets across the sodium-bearing interlayer region. The amount of the layer offset is about 0.9 Angstrom (ca. a/6) and the direction is one of [(1) over bar oo], [110] and [1 (1) over bar0]. These directions are occasionally disordered. By combination of the intralayer shift and layer offset, the ordered aspidolite has different one-layer structures with monoclinic ([(1) over bar 00] layer offset) and triclinic ([110] or [1 (1) over bar0] layer offset) cells. The proposed cell dimensions are a = 5.30, b = 9.18, c = 10.12 Angstrom, beta = 105.3degrees for the monoclinic (C2/m) cell and a = 5.30, b = 9.18, c = 9.88 Angstrom, alpha = 94.4, beta = 97.8, gamma = 90degrees for the triclinic (C (1) over bar) cell. Both structures were identified in powder X-ray diffraction patterns and probably the triclinic structure is more common. This is the first report that structural variations are generated in micas by the combination of the intralayer shift and layer offset.
Keywords: aspidolite